Education for all: A local SDG 4 journey at Tambunan Bondulu Toboh Home - Wong Sing Yun; Jain Yassin; Suddin Lada; Mat Salleh Ayub; Siti Nor Bayaah Ahmad; Brahim Chekima; Faerozh Madli; Rudy Ansar; Lim Ming Fook (Human Resource Management Academic Research Society, 2023)
SDG 4 Quality Education was one of the 17 global goals set by the United Nations in the 2030 Agenda for Sustainable Development with the main objective to ensure inclusive and equitable quality education and promotion of lifelong learning opportunities for all. Marginalized groups are often disproportionately deprived of SDG 4's benefits due to various social, economic, and political barriers that hinder their access to quality education and lifelong learning opportunities. Governments, international organizations, and civil society must undertake focused initiatives to address these inequities and advance inclusive education. The education program undertaken in Bondulu Toboh Children’s Home was of a good initiative example that involves collaboration between the bi-partisan organization APPGM-SDG with the local education institutions. The collaborative effort that involves pooling resources and expertise can provide better learning opportunities for vulnerable communities to thrive academically and potentially break down the barriers of education inequalities. This research will primarily delve into analyzing the benefit of such an initiative that was aligned directly with SDG 4. Extending beyond that, this program can empower marginalized students to break the cycle of poverty and contribute positively to society’s progress and development.